2023
DOI: 10.1177/07356331221137107
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between ICT Perceived Competence and Adolescents’ Digital Reading Performance: A Multilevel Mediation Study

Abstract: The age of information and communication technology (ICT) has witnessed the prevalence of computer-based reading. Previous studies yielded mixed results concerning the relationship between ICT perceived competence, ICT use and digital reading performance, and the underlying mechanism was rarely explored. This study aimed to explore the relationship between ICT perceived competence and adolescents’ digital reading performance and the potential mediating roles of three types of ICT use. Multilevel mediation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 83 publications
2
0
0
Order By: Relevance
“…Additionally, this research examined the relationship between PERCEIVED ICT and ten variables believed to be associated with it, and it was found that the level of ICT resources, interest in ICT, and ICT use for social interaction significantly predicted PERCEIVED ICT. The highest impact was observed between PERCEIVED ICT and ICT use for social interaction, aligning with the findings of Yu et al (2023). In this study, it was also found that students with a higher perceived ICT competence tend to use ICT more in their free time at home.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 87%
“…Additionally, this research examined the relationship between PERCEIVED ICT and ten variables believed to be associated with it, and it was found that the level of ICT resources, interest in ICT, and ICT use for social interaction significantly predicted PERCEIVED ICT. The highest impact was observed between PERCEIVED ICT and ICT use for social interaction, aligning with the findings of Yu et al (2023). In this study, it was also found that students with a higher perceived ICT competence tend to use ICT more in their free time at home.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 87%
“…Furthermore, among adolescents, perceived health literacy has been shown to correlate well with measured health literacy 16 . A similar link between perceived and measured competencies has been found in several PISA studies, such as those on digital reading 17 and mathematics 18 .…”
Section: Introductionsupporting
confidence: 79%